Kualiti Dan Kepuakkan Dalam Politik : Rujukan Khusus Ke Atas UMNO Dan Pentadbiran Kerajaan Negeri Kedah - Abdul Rahman, Ibrahim (2000)
UMNO which has been established on May 11 1946 has emerged as the Malay dominant political party and backbone of National Front Government to reign the country. Its ability due to politic of coalition, unity and a clear policy which managed to implement by its leaderships. In situation where idealism, aspiration and needs of the people can be articulate in clear manner by its leaders, hence it vital to support the present leadership for achieving the party mission, On the contrary, during image, accountability and performance of the party has been tarnish, such of mechanism such as the practice of politics of factionalism is require in enhancing the party back into the right direction. Therefore, this study is put forward as an alternative discussion to show how the practice of politics factionalism in the context of UMNO will overcome and reengineering the unity, strengthening government machinery at a state and national level. These was the basic things that will’ be analyze by focusing the practice of politics factionalism specifically in the context of Kedah’s UMNO.